2004
DOI: 10.1167/iovs.03-1113
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like Receptor 4 and Its Associated Lipopolysaccharide Receptor Complex by Resident Antigen-Presenting Cells in the Human Uvea

Abstract: The present study demonstrates for the first time that resident APCs in the normal human uvea express TLR4 and its associated LPS receptor complex. This has significant implications for the understanding of normal ocular immunity as well as unraveling the potential role of Gram-negative bacteria in the pathogenesis of acute anterior uveitis (AAU).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
57
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 35 publications
4
57
2
Order By: Relevance
“…31 In contrast with our findings, 28 however, Brito et al also reported TLR4 protein staining on the non-pigmented epithelial cells of the ciliary body and in the superficial layers of the retina. 31 We had also observed a similar pattern of staining when using paraffin embedded ocular sections (which were not observed in our studies using fresh frozen sections 28 ) and these were considered to be non-specific, as we observed an identical pattern of positive staining using the isotype matched negative control antibody (unpublished data).…”
Section: Uveacontrasting
confidence: 99%
See 4 more Smart Citations
“…31 In contrast with our findings, 28 however, Brito et al also reported TLR4 protein staining on the non-pigmented epithelial cells of the ciliary body and in the superficial layers of the retina. 31 We had also observed a similar pattern of staining when using paraffin embedded ocular sections (which were not observed in our studies using fresh frozen sections 28 ) and these were considered to be non-specific, as we observed an identical pattern of positive staining using the isotype matched negative control antibody (unpublished data).…”
Section: Uveacontrasting
confidence: 99%
“…We proposed that this may reflect the unique immunologically privileged nature of the eye. 28 Recently, Brito et al confirmed our findings with the detection of TLR4+ cells in the uveal stroma that were ''probably resident macrophages and DCs.'' 31 In contrast with our findings, 28 however, Brito et al also reported TLR4 protein staining on the non-pigmented epithelial cells of the ciliary body and in the superficial layers of the retina.…”
Section: Uveasupporting
confidence: 78%
See 3 more Smart Citations